Poland and Greece - Two Contrasting EU Enlargement Experiences - Ryszard Rapacki (ZEI, 2012)
The aim of this contribution is a comparative analysis of the challenges Poland and Greece (and more broadly – CEE-10 and GIPS countries) had to face in the past as latecomers to the European Union and are facing now, in the aftermath of the world financial and economic crisis of 2008-09.
Keywords: O1; F15; 330; European union; economic development; European union; economic development